2011
DOI: 10.1007/s12033-011-9421-7
|View full text |Cite
|
Sign up to set email alerts
|

RAPD Fingerprint to Appraise the Genetic Fidelity of In Vitro Propagated Araucaria excelsa R. Br. var. glauca Plantlets

Abstract: Randomly amplified polymorphic DNA (RAPD) was used as a tool to assess the genetic fidelity of in vitro propagated Araucaria excelsa R. Br. var. glauca with explants taken from orthotropic stem along with their related mother plants after treatment with kinetin, 2iP, BA (0.02-0.26 mg/l) and TDZ (0.001-1 mg/l) to produce axillary shoots. TDZ and kinetin induced more shoot and higher length per explant. Results showed a total of 1,676 fragments were generated with 12 RAPD primers in micropropagated plants and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…(Prakash et al, 2004), Cymbopogon flexuosus (Bhattacharya et al, 2008), papaya (Homhuan et al, 2008) and cotton (Jin et al, 2008). Also, there are several reports about TDZ affecting the DNA stability of plants propagated in vitro (Sarmast et al, 2012;Roy et al, 2012;Khattab et al, 2014). In contrast, the RAPD analysis performed in our study detected no polymorphism within plants regenerated through the same regeneration pathway, whereas the RAPD analysis with the same decamer primers revealed considerable polymorphism within iris plants derived from seeds.…”
Section: Discussioncontrasting
confidence: 68%
“…(Prakash et al, 2004), Cymbopogon flexuosus (Bhattacharya et al, 2008), papaya (Homhuan et al, 2008) and cotton (Jin et al, 2008). Also, there are several reports about TDZ affecting the DNA stability of plants propagated in vitro (Sarmast et al, 2012;Roy et al, 2012;Khattab et al, 2014). In contrast, the RAPD analysis performed in our study detected no polymorphism within plants regenerated through the same regeneration pathway, whereas the RAPD analysis with the same decamer primers revealed considerable polymorphism within iris plants derived from seeds.…”
Section: Discussioncontrasting
confidence: 68%
“…Explants grown in medium supplemented with TDZ, were morphologically better than other explants treated with plant growth regulators (PGRs) (Fig. 2), hence the explants treated with TDZ were used for further experiments [17]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The potting medium consisted of a 1:1:1 (in volume) of loam, peat moss, and perlite and it was fertilized by Kristalon solution (1/1000, each 15 days). Four cm of apical stem segments of main stem were cut from seedlings and kept under running tap-water for 2 h. Because of high contamination rate, nano silver (NS) with concentration of 500 µg/ml under reduced pressure (300 mm Hg in 5 min) [16,17] was used to eradicate bacterial contamination. Then, the explants were treated with 70% ethanol for 3 min and 15% Clorox (containing 5.25% sodium hypochlorite) with 0.2% detergent for 10-20 min for surface sterilization, and then rinsed six times with sterilized distilled water.…”
Section: Decontamination Of Explants and Production Of Orthotropic Shmentioning
confidence: 99%
“…Regarding to PGRs, MNS/E was not always correlated to MLS/E. It is shown that higher concentration of PGRs especially cytokinins results in somaclonal variation in plants (Hartmann et al 2011;Sarmast et al 2012). The highest axillary shoots formation ability occurred on MS medium supplemented with Fig.…”
Section: Discussionmentioning
confidence: 96%